Smarter Grid in the 5G Era: A Framework Integrating Power Internet of Things With a Cyber Physical System - Liu, Yuanjie; Yang, Xiongping; Wen, Wenkun; Xia, Minghua (Frontiers in Communications and Networks, 2021)
As the energy infrastructure of smart cities, smart grid upgrades traditional power grid systems with state-of-the-art information and communication technologies. In particular, as the full deployment of the Internet of Things in the power grid (a.k.a. power Internet of Things or PIoT), the newly introduced information flow together with inherent energy flow, makes more efficient power generation, transmission, distribution, and consumption. To further exploit the precious energy and the latest 5G technologies, this article boosts to add a value flow in the smart grid, mainly including the value created by innovative services and market mechanisms and the value added by the information flow. Specifically, by integrating PIoT with cyber-physical systems, this article develops a conceptual framework of the cyber-physical power system (CPPS). The resulting CPPS carries out holistic perception and ubiquitous connection of distributed energy sources and electrical facilities and builds up a smarter power grid with global information interaction, intelligent decision-making, and real-time agile control. Finally, for illustration purposes, a case study regarding an intelligent home management system is conducted.